2006
DOI: 10.1897/1551-3793(2006)2[330:ctrtae]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Risks to Aquatic Ecosystems: A Tentative Approach in the Context of Freshwater Dredged Material Disposal

Abstract: The development of relevant frameworks for assessing ecological risks posed by dredged material management does not only involve an appropriate selection of assessment and measurement endpoints but also requires a sound approach to both risk characterization and the associated uncertainty. A formal methodology addressing both aspects has been developed in France for freshwater sediment deposits in water. Both exposure and effects measurements are 1st transformed into scores or classes. As far as possible, clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Only The Netherlands has established quality criteria for the interpretation of results, although this approach seems recommended when broad databases are available for its development and especially for screening methodologies. Otherwise, the use of the statistical difference from a control or reference sediment avoids arbitrary differences in the classification of dredged materials between countries while allowing us to determine between different intensities of responses to different statistical probabilities that may be used afterwards in ecological risk assessment frameworks (Babut et al 2006). Nevertheless, the selection of the reference sediment to which results are compared could introduce major differences in the final classification of the sediments, while offering the possibility to interpret the results in terms of site‐specific conditions.…”
Section: Application Of Action Levels For the Management Of Dredged Mmentioning
confidence: 99%
“…Only The Netherlands has established quality criteria for the interpretation of results, although this approach seems recommended when broad databases are available for its development and especially for screening methodologies. Otherwise, the use of the statistical difference from a control or reference sediment avoids arbitrary differences in the classification of dredged materials between countries while allowing us to determine between different intensities of responses to different statistical probabilities that may be used afterwards in ecological risk assessment frameworks (Babut et al 2006). Nevertheless, the selection of the reference sediment to which results are compared could introduce major differences in the final classification of the sediments, while offering the possibility to interpret the results in terms of site‐specific conditions.…”
Section: Application Of Action Levels For the Management Of Dredged Mmentioning
confidence: 99%
“…It was found that the paralysis appeared after two to three weeks of exposure (Dinham, 1993). In agricultural areas, huge amounts of pesticides can be drained by storm water and discharged into nearby rivers plantations, jeopardizing, not only the survival of exposed organisms, but also the quality of these waters (Marchand, 1989;Monkiedje et al, 2004;Babut et al, 2006). Tests performed in laboratory microcosm, had previously shown different levels of tolerance of aquatic organisms to pesticides exposure (Monod, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Most industrialized countries regulate and manage contaminated sediments and dredged materials in their waterways. Consequently, various ecological risk assessment (ERA) approaches have been developed, and sediment quality guidelines (SQGs) were included in many cases (Babut et al 2005, 2006; Alvarez‐Guerra et al 2007; Apitz et al 2007). In Canada, Environment Canada regulates ocean and estuarine dredging operations and open‐water disposal through Environment Canada's Disposal at Sea Program (DAS) under the Canadian Environmental Protection Act, 1999 (CEPA 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most industrialized countries regulate and manage contaminated sediments and dredged materials in their waterways. Consequently, various ecological risk assessment (ERA) approaches have been developed, and sediment quality guidelines (SQGs) were included in many cases (Babut et al , 2006Alvarez-Guerra et al 2007;Apitz et al 2007). In Canada Act, 1999(CEPA 1999.…”
Section: Introductionmentioning
confidence: 99%